Genomic and transcriptomic insights into vitamin A-induced thermogenesis and gene reuse as a cold adaptation strategy in wild boars - Mingpeng Zhang; Aleksei Traspov; Jiawen Yang; Min Zheng; Veronika R. Kharzinova; Huashui Ai; Natalia A. Zinovieva; Lusheng Huang (Communications Biology)
Abstract Wild boars inhabit diverse climates, including frigid regions like Siberia, but their migration history and cold adaptation mechanisms into high latitudes remain poorly understood. We constructed the most comprehensive wild boar whole-genome variant dataset to date, comprising 124 samples from tropical to frigid zones, among which 47 Russian, 8 South Chinese and 3 Vietnamese wild boars were newly supplemented. We also gathered 75 high-quality RNA-seq datasets from 10 tissues of 6 wild boars from Russia and 6 from southern China. Demographic analysis revealed the appearance of Russian wild boars in Far East of Asia (RUA) and Europe (RUE) after the last glacial maximum till ~ 10 thousand years ago. Recent gene flow (<100 years) from RUA to RUE reflects human-mediated introductions. Cold-region wild boars exhibit strong selection signatures indicative of genetic adaptation to cold climates. Further pathway and transcriptomic analyses reveal a novel cold resistance mechanism centered on enhanced vitamin A metabolism and catalysis, involving the reuse of UGT2B31 and rhythm regulation by ANGPTL8, RLN3 and ZBTB20. This may compensate for the pig’s lack of brown fat/UCP1 thermogenesis. These findings provide new insights into the molecular basis of cold adaptation and improve our understanding of Eurasian wild boar migration history.